ADVISING ON YOUTH ENTREPRENEURSHIP TO ENSURE SUSTAINABLE ECONOMIC DEVELOPMENT (Innovative professional education, 2024)
The article substantiates the essence of youth entrepreneurship counselling as a complex interactive strategy for assisting future entrepreneurs in achieving success. Such a strategy is a holistic, unique system, which can be presented as a joint effective activityof a vocational education student and a teacher-consultant. The main product of such activity is effective changes in the consciousness of students of vocational education and training, their attitude to future business activities, minimisation of problematic aspects of their civilisation, overcoming uncertainty, difficulties in mastering the basics of financial literacy and entrepreneurship, improvement of the emotional sphere,optimisation of personal qualities.
Keywords: youth entrepreneurship, professional education, consulting on youth entrepreneurship, entrepreneurial activity, students of professional (vocational and technical) education